(untitled) (Revista NUPEART, 2025)
This writing deals with biographical aspects of the cirandeira Lia de Itamaracá with critical reflections on this trajectory and reinforces the contributions that the master presents to Brazilian culture in contemporary times. With actions marked by the resistance of a black and peripheral woman, the paths were full of setbacks and confrontations that today lead to the consolidation of an artistic reference that makes up knowledge and practices in the field of art and culture. The article is part of the author’s master’s degree (2014-2016) and doctorate (2019-2023) studies and was created based on a bibliographical review, interviews, analysis of documentaries and, especially, the writing of her own body in Ciranda’s circles.